UJI EFEK PENGUMUMAN RIGHTS OFFERINGS/RIGHTS ISSUEPADA PASAR SAHAM INDONESIAPERIODE 2012-2016 - DICKY MARKUS ANGKASAJAYA; Putu Anom Mahadwartha; Endang Ernawati (Perpustakaan Universitas Surabaya, 2018)
The purpose of this study is to examine how the market will react to rights offerings/rights issue announcement day (at extraordinary general meeting). This study used the company data listed on Indonesian Stock Exchange (BEI) from period 2012-2016 who has held rights offerings/rights issue. This study uses event study methodology to observe the abnormal return and cumulative abnormal return that occurred around the rights offerings/rights issue announcement day (at extraordinary general meeting). This study found that abnormal return would occur sorrounding the announcement date (t-1 for discounted rights offerings and t+3 for premium rights offerings). Both types of offerings show that investors will give a positive reaction about the rights offerings. This study also found that cumulative abnormal return would occur arround the announcement date (t-3 to t+3) and investors will be benefited if they buy that stock at three days before and sell it at three days after rights offerings announcement.